Le parquet dans la magistrature - Isabelle Boucobza (Laboratoire Italien, 2001)
The issue of the independence of prosecution is a focal debate in France and Italy. The fact that prosecutors are members of the magistracy is at the origin of a controversy in those countries, as some consider them an organ of the executive power while others consider them an organ of the judicial power. The actors of the debate –politicians, magistrates, law professors– all develop an elaborate juridical argumentation to support their theses. Going through the analysis of the arguments put forward by the confronting parties and highlighting the motivations for those, this paper aims at making explicit the reasons for the ambiguity of the role and of the statute of the prosecutor in the magistracy. Particularly, this study intends to demonstrate that, regardless of the thesis supported, it is impossible for the actors of the debate to conceive the function of the prosecutor without also thinking of the function of the judge through the concept of “magistrate”. It is the conception of the role of the judge-magistrate that ends up determining the fate of prosecution.